Georges Devereux et l’ethnopsychiatrie : fonder sa science et assurer sa consécration - Alessandra Cerea (Revue d’Histoire des Sciences Humaines)
Georges Devereux’s Seminar, held at the EHESS in Paris in 1963, institutionalised Ethnopsychiatry in Europe, and was followed by the translation of his writings, first published in the United States, into French. This article reconstructs the history of this phenomenon using archival sources. It shows how Devereux’s public success as ‘father’ of Ethnopsychiatry was due to a convergence of specific factors, combined with fortunate institutional and editiorial choices, and the socio-cultural climate of 1960s France in which the discipline burgeoned. Devereux contributed to his own consecration, and also to reworking and translating his own writings. More broadly, he was active in founding Ethnopsychiatry as a reflection on the universality of the human spirit.